Trade reforms and trade patterns in Latin America - Ventura-Dias, Vivianne (ECLAC SantiagoCL, 1999)
Examines the trade performance of 16 Latin American countries over the past 20 years using a modified Pavitt-Guerrieri classification to group trade data according to the technological content of the production functions of individual goods. Discusses some of the difficulties in classifying goods according to their production functions when production sharing prevails in international trade.